1999
DOI: 10.1099/00222615-48-3-287
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic similarity of multiresistant Acinetobacter baumannii isolates in the Czech Republic

Abstract: The diversity of 103 clinical isolates of the Acinetobacter calcoaceticus-Acinetobacter baumannii complex obtained between 1991 and 1997 from 17 Czech hospitals was studied by ribotyping, biotyping, plasmid profiling and antibiotic susceptibility testing. According to the EcoRI ribotypes, all but one of these isolates were identified to the DNA group level: 77 isolates were allocated to DNA group 2 (A. baumannii), 14 to DNA group 3, 10 to DNA group 13 sensu Tjernberg and Ursing and one to DNA group 1 (A. calco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
51
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 28 publications
7
51
0
1
Order By: Relevance
“…According to recent studies, A. baumannii have resistance to β-lactams, the extended spectrum cephalosporin, tobramycin, amikacin and fluoroquinolone [20][21][22] . Carbapenem antibiotics such as imipenem are useful treatments for Gram negative strains having resistance to β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, A. baumannii have resistance to β-lactams, the extended spectrum cephalosporin, tobramycin, amikacin and fluoroquinolone [20][21][22] . Carbapenem antibiotics such as imipenem are useful treatments for Gram negative strains having resistance to β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…Four AFLP genotypes (clones) were identified, of which two genotypes, clones I and II, were responsible for most outbreakassociated infections in the countries examined (4). A further study in the Czech Republic published in 1999 also identified two predominant outbreak-associated clones, groups A and B, that corresponded to the two clones identified in other northern European countries (10).…”
mentioning
confidence: 99%
“…AFLP cluster 7 contained strains belonging to European clone II, with the exception of isolate GNU1086, which was located in AFLP cluster 8. In previous studies, clone I and group A isolates were identified in four United Kingdom centers and were also identified in Belgium, the Czech Republic, and The Netherlands (4,10). Clone II and group B isolates were located in three United Kingdom centers and were also identified in Denmark, the Czech Republic, and The Netherlands (4,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the pheno-and genotypic similarities among A. baumannii strains isolated in the Czech Republic were analyzed (12). Based on the results, these isolates could be classified into four groups: two relatively homogeneous groups of predominantly multiresistant strains (termed groups A and B) comprising both sporadic and outbreak-associated isolates, a heterogeneous group of other multiresistant strains, and a group of mainly susceptible strains (12).…”
mentioning
confidence: 99%